Humic substances decrease the stress in layer hens during the post molting phase - Sanmiguel-Plazas, Rosa Angélica; Rodríguez-Niño, Claudia Alexandra; Aguirre-Pedreros, Wilson Javier (Universidad Pedagógica y Tecnológica de Colombia, 2015)
One of the productive practices in laying hens that causes controversy in the animal welfare area is the nutritional stress produced during the forced molt phase. The current research relates the experiment implemented to evaluate the effect of the Humic Substances (HS) on stress indicators during the post molting phase. 120 HyLine Brown laying hens were observed within the 60 first days of the post molting, which were divided in four groups: the first and second were supplemented with 0,1 and 0,2% of HS respectively, the third group was supplemented with 0,25 mg/kg of hydrochloride of levamisole, and the fourth was not supplemented at all; blood samples were taken the days 8, 30 and 60 to evaluate hematocrit and Heterophils/Lymphocytes relationship (H/L) and the tonic immobility was recorded from the days 30"‘ and 60"”. It was evidenced that the groups supplemented with HS improved the hematocrit by the day 30*, decreased the H/L relationship and the tonic immobility time days 30‘“ and 60‘“ (p<0,05).The results obtained in this research indicate that the HS from the cachaza, leaves and vinasse from the sugar production, perform as stress reliever agents in the early and middle phase of the post molting in Hy Line Brown laying hens.